Effects of Self-Massage and Foot Exercises on Lumbar Spine Pain and Functional Condition in Sedentary Men - Adrija Gorodeckaitė; Ligita Šilinė (Lithuanian Sports University, 2022)
Background. Lumbar pain is one of the most common disorders of the musculoskeletal system in workers who sit for prolonged periods of time. Prolonged sitting hours change muscle activity and create tension, which negatively affects the structure of the fascia. Myofascial exercises for the posterior superficial chain have been shown to reduce lumbar pain, but the effect of self-massage and foot exercises on the functional condition of the lumbar in office workers is unclear. The aim. To assess the effect of self-massage and foot exercises on lumbar pain and functional condition in male office workers. Methods. The study included 20 men (25.8 ± 2,6 year) (10 in the experimental group, 10 in the control group) engaged in sedentary work and experiencing chronic non-specific lumbar pain. Before and after the study, a pain intensity assessment was performed using the numerical rating scale (NRS), a functional status assessment using the Oswestry questionnaire, and an assessment of the superficial length of the back superficial chain (lower part) using the toe reach test. For the experimental group, 5 times a week for 10 weeks for 10 minutes, self-massage was applied to each foot; and 3 times a week for 30 minutes, exercises for the feet. Results. After self-massage and foot exercises, the intensity of pain and functional disability decreased significantly (p <0.001), and the length of the back superficial chain (lower part) increased (p <0.001). Functional disability increased in the control group (p <0.001). After the study, functional disability differed significantly between groups (p = 0.02). Conclusion. Self-massage and foot exercises improved functional condition and reduced lumbar pain in male office workers. Keywords: low back pain, fascia, myofascial chain, massage, physiotherapy.